Proceedings of the 7th International Scientific Conference Rural Development 2015 2015
DOI: 10.15544/rd.2015.031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Uv-a Supplemental Lighting on Antioxidant Properties of Ocimum Basilicum L. Microgreens in Greenhouse

Abstract: The effects of supplemental UV-A LED lighting on growth and antioxidant properties of two varieties of basil (Ocimum basilicum L.) microgreens were determined. Purple-leaf ‘Dark Opal’ and green-leaf ‘Sweet Genovese’ basils were grown in greenhouse (14 days, 22/18 ± 2 °C day/night temperature, 40 ± 5 % a relative air humidity) during winter season. The main lighting system (HPS lamps and natural daylight) was supplemented with ~13.0 μmol m-2 s-1 flux of UV-A 390 nm, and a total PPFD was ~125 μmol m-2 s-1 (16 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…Similarly, Goto et al (2016) obtained an increase in anthocyanins exposing red leaf lettuce to three different UV wavelengths in the order 310 nm >325 nm >340 nm. In contrast to that, Vaštakaitë et al (2015a) showed that anthocyanin content in basil was highest without UV radiation. Similarly, exposing basil to three supplementary UV wavelengths at two intensities, the group of Brazaitytë et al (2015) found highest content of anthocyanins in the control group.…”
Section: Anthocyaninscontrasting
confidence: 59%
See 1 more Smart Citation
“…Similarly, Goto et al (2016) obtained an increase in anthocyanins exposing red leaf lettuce to three different UV wavelengths in the order 310 nm >325 nm >340 nm. In contrast to that, Vaštakaitë et al (2015a) showed that anthocyanin content in basil was highest without UV radiation. Similarly, exposing basil to three supplementary UV wavelengths at two intensities, the group of Brazaitytë et al (2015) found highest content of anthocyanins in the control group.…”
Section: Anthocyaninscontrasting
confidence: 59%
“…Rodriguez et al (2014) determined an increased concentration of flavonols in lettuce using supplemental UV FL-Tubes additional to sunlight and supplemental HPSL. Similarly, basil was exhibiting a higher flavonol content when being illuminated with 13 µmol/m 2 /s at 390 nm for 7 and 14 days before harvest (Vaštakaitë et al, 2015a). Brazaitytë et al (2015) found out that supplemental 6 or 12 µmol/m 2 /s at a wavelength of 402 or 390 nm, respectively, produced best results regarding flavonol index.…”
Section: Flavonolsmentioning
confidence: 96%
“…The rapid development of UV-emitting diodes makes it possible to add single UV-A wavelengths to the light spectrum in CEA lighting, which enables a more accurate assessment of the effect of those single wavelengths. Only few studies have been published on the effects of UV-A on vegetables, and these studies show stimulatory effects of UV-A on the growth of some vegetables (Brazaitytė et al, 2010; Chang and Chang, 2014; Khoshimkhujaev et al, 2014; Brazaitytė et al, 2015; Mickens et al, 2019) but inhibitory (Brazaitytė et al, 2009; Vaštakaitė et al, 2015; Jensen et al, 2018) or no effects on others (Li and Kubota, 2009). Our investigations with a standard visible LED lighting system revealed a positive effect of 390-nm UV-A (for 10 h) and 402-nm UV-A (for 10 and 16 h) on the leaf area of mustard microgreens ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the application of UV-A radiation has been shown to have an uneven effect on AA accumulation in leafy vegetables. For example, UV-A radiation had no effect on the AA content of baby leaf lettuce (Li and Kubota, 2009) and pea seedlings (Liu and Yang, 2012; Wenke and Qichang, 2012) increased its content in green and purple basil ( Ocimum basilicum ) (Vaštakaitė et al, 2015) and red pak choi and decreased its content in beets and basil-cultivated indoors (Brazaitytė et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation